2020
DOI: 10.1155/2020/6925107
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Detection in EEG Signals: A Case Study on Similarity Measure

Abstract: Motivation. Anomaly EEG detection is a long-standing problem in analysis of EEG signals. The basic premise of this problem is consideration of the similarity between two nonstationary EEG recordings. A well-established scheme is based on sequence matching, typically including three steps: feature extraction, similarity measure, and decision-making. Current approaches mainly focus on EEG feature extraction and decision-making, and few of them involve the similarity measure/quantification. Generally, to design a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…It may be possible to improve classification performance further using other types of similarity measures. For example, in a recent study, Hellinger distance and Bhattacharyya distance showed their effectiveness with highly noisy EEG signals (Chen G. et al, 2020 ). Although comparisons between different approaches of similarity measures are beyond the scope of this study, they certainly merit attention in evaluating the effectiveness of using different between-run similarity measures as neurophysiological features for classifying neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be possible to improve classification performance further using other types of similarity measures. For example, in a recent study, Hellinger distance and Bhattacharyya distance showed their effectiveness with highly noisy EEG signals (Chen G. et al, 2020 ). Although comparisons between different approaches of similarity measures are beyond the scope of this study, they certainly merit attention in evaluating the effectiveness of using different between-run similarity measures as neurophysiological features for classifying neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Since working memory tasks are presumably more cognitively exhausted for the MCI or AD group than the HC group, we hypothesize that the difference in the neurophysiological patterns of the before-task and after-task “resting-state” in the brain will be larger for the MCI group than the HC group, and such difference carries more discriminative information for classification in comparison with the approach using single-run resting-state EEGs that has been adopted in previous studies related to the MCI-HC classification. To achieve this goal, we designed a novel feature extraction framework in which we introduced the delayed matching-to-sample (DSTM) task as a cognitively challenging behavior test, applied a similarity-based approach (Chen G. et al, 2020 ) to quantitatively evaluate the task-induced intra-subject variation of resting-state EEG powers, and used it as a neural marker to classify between the MCI and HC groups. To the best knowledge of the authors, this is the first study that focuses on the analysis of task-induced intra-subject variability between two separate runs of resting-state EEGs for the detection of MCI.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the proposed method can be framed into the anomaly and point change detection research areas. In a broad sense, 'anomaly detection refers to the problem of finding patterns in data that do not conform to expected behavior' [21] and it has found application in various fields and for a long time [22][23][24][25]. Anomaly detection is a highly applicationoriented problem [26] and several approaches have been proposed to solve it, depending on research disciplines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The correlation does not vary with distance in a linear trend as is habitually deemed, but rather a non-linear fashion. To demonstrate this counterintuitive relation, the Hellinger Distance (Chen et al, 2020 ) from two SEEG channels and the target EEG channel are compared as shown in Figure 3 . The leftmost column gives an example of what a matching strategy is expected to solve.…”
Section: Methodsmentioning
confidence: 99%